Spectrum of Hospital Acquired Acute Kidney Injury in Critically ill Children in a Tertiary Level Hospitall - Huque, Syed Saimul; Begum, Afroza; Rahman, Md Habibur; Uddin, Golam Muin; Roy, Ranjit Ranjan; Mannan, Md Abdul; Islam, Md Afiqul; Kawser, Chowdhury Ali (Journal of Pediatric Nephrology, 2018)
Introduction: Although hospital acquired acute kidney injury (hAKI) is common and significantly increases the risk of hospital mortality, little is known about its frequency in developing countries where ICU facilities are limited. The purpose of this study was to investigate the frequency, cause, and outcome of hAKI in critically ill children in a tertiary level hospital. Materials and Methods: In this prospective cross-sectional study, a total 36 critically ill patients with hAKI were analyzed. hAKI was diagnosed according to the AKIN criteria. The clinical data of the patients admitted to the Pediatrics and Allied Departments in this hospital from November 2014 to October 2015 were collected. Results: A total of 3950 patients were admitted during the study period and 1103 (27.9%) were critically ill patients. Among the critically ill children, 36 (3.3%) were diagnosed with hAKI. Among different age groups, the highest incidence (5.05%) of hAKI was seen in children aged above 10 years. Sepsis was the major cause of hAKI accounting for 44.1% followed by antibiotics (27.1%), hypovolemia (13.6%), nephrotoxic agents (10.2%), and contrast agents (5.0%). Renal replacement therapy was required only in 8.3% of the cases. Conclusions: In comparison to other studies, this study showed a low incidence of hAKI where ICU facilities are limited. Among the hospital admitted critically ill patients, a significant number of patients may develop AKI mostly due to sepsis and use of antibiotics. Keywords: Hospital acquired AKI; Sepsis; Critically ill children; Incidence